{uFE97}{uFEE8}{uFEE4}{uFEF4}{uFE94} {uFE8D}{uFEDF}{uFE98}{uFED4}{uFEDC}(3jQ (B{u(3FE8D(B}{u(3FEFB(B}{u(3FE91(B}{u(3FE98(B}{u(3FEDC(B}{u(3FE8E(B}{u(3FEAD(B}(3i (B{u(3FEDF(B}{u(3FEAA(B}{u(3FEEF(B} {u(3FE8D(B}{u(3FEF7(B}{u(3FEC3(B}{u(3FED4(B}{u(3FE8E(B}{u(3FEDD(B} {u(3FEAB(B}{u(3FEED(B}(3i (B{u(3FEBB(B}{u(3FECC(B}{u(3FEEE(B}{u(3FE91(B}{u(3FE8E(B}{u(3FE95(B} {u(3FE8D(B}{u(3FEDF(B}{u(3FE98(B}{u(3FECC(B}{u(3FEE0(B}{u(3FEE2(B} {u(3FE8D(B}(3deh(B{u(3FEEB(B}{u(3FEEE(B}{u(3FE91(B}(3jf (B{u(3FE91(B}{u(3FE8E(B}{u(3FEB3(B}{u(3FE98(B}{u(3FEA8(B}{u(3FEAA(B}{u(3FE8D(B}{u(3FEE1(B} {u(3FE91(B}{u(3FEAE(B}{u(3FEE7(B}{u(3FE8E(B}{u(3FEE3(B}{u(3FE9E(B} {u(3FEB3(B}{u(3FEDC(B}{u(3FE8E(B}(3eHQ (B/ s - (3jGSQ MeOi Rci eMeOs; {uFE87}(3jeG(B{u(3FEE5(B} {u(3FEB3(B}{u(3FECC(B}{u(3FEF4(B}{u(3FEAA(B} {u(3FECB(B}{u(3FE92(B}{u(3FEAA(B}{u(3FE8D(B}(3dMejO (B: s; {uFEA7}{uFE8E}{uFEDF}{uFEAA} {uFECB}{uFE92}{uFEAA}{uFE8D}{uFEDF}{uFEAE}{uFE8D}{uFEAF}{uFED5} {uFE8D}{uFEDF}{uFEE8}{uFEA0}{uFE8E}{uFEAD} ((3GdbGgQI (B: s {uFEF3}{uFE8E}{uFEB3}{uFEAE} (3MeOi (B{u(3FEAF(B}(3ci (B{u(3FEE4(B}(3MeO (B: s, 2016)
(3JgOa GdOQGSI Gdi eMGhdI GdJMbb ef aGYdjI HQfGeL ScGejQ ai JfejI GdJacjQ GdGHJcGQi dOi GdCWaGd Phi UYhHGJ GdJYde GdehghHjf(B: (3h JchfJ YjfI GdOQGSI ef (B(8) (3CWaGd GdedJMbjf HQhVI eOQSI Gdfjd GdNGUI GdJGHYI dEOGQI GdYeQGfjI GdJYdjejI(B: (3h jYJeO GdHMK Ydi fJGFL GdbjGS GdbHdi h GdHYOi dYjfI GdOQGSI(B: (3h GSJNOGe GdHGMK GdefgL (B((3THg GdJLQjHi(B) (3dJMOjO aGYdjI GSJNOGe HQfGeL ScGejQ ai JfejI GdJacjQ GdGHJcGQi YfO GdCWaGd Phi UYhHGJ GdJYde GdehghHjf(B: (3h Pdc HbjGS CKQ GdeJZjQ Gd eSJbd (B((3HQfGeL ScGejQ(B) (3Ydi GdeJZjQ GdJGHY (B((3GdJacjQ GdGHJcGQi(B) (3h GSJNOGe GdHGMK COhGJ YOIh gi ebjGS bGFeI UYhHGJ GdJYde GdfeGFjI (B((3YGOd YHOGddg(B) (3h ebjGS GdcTa Yf GdehghHjf aieQMdI eG bHd GdeOQSI (B((3SdajG Qje(B) (3GNJjGQ JhQGfS ddJacjQ GdGHJcGQi HGSJNOGe GdMQcGJ h GdCaYGd (B( (3Hhd JhQGfS JQLeI eMeO KGHJ h HQfGeL ScGejQ dJfejI GdJacjQ GdGHJcGQi (B((3GdeYOd(B) (3EYOGO (B((3GdHGMK(B) (3h bO CTGQJ GdfJGFL Edi hLhO aQhb PGJ OdGdI Hjf eJhSWGJ QJH OQLGJ GdCWaGd Phi UYhHGJ GdJYde GdehghHjf ai GdbjGSjf GdbHdi h GdHYOi HYO JWHjb HQfGeL ScGejQ Ydi ebjGS GdJacjQ GdGHJcGQi dUGdM GdbjGS GdHYOi h dG JhLO aQhb PGJ EMUGFjI Hjf eJhSWGJ QJH OQLGJ GdCWaGd Phi UYhHGJ GdJYde GdehghHjf ai GdbjGSjf GdHYOi h GdJJHYi HYO JWHjb HQfGeL ScGejQ Ydi ebjGS GdJacjQ GdGHJcGQis
(3GWQhMI (B((3OcJhQGg(B) - (3LGeYI GdbGgQI (B- (3cdjI GdJQHjI ddWahdI GdeHcQI (B- (3bSe GdYdhe GdfaSjIs
(3UOQ GjVG cbQU eOeLs
Keywords: (3GdCWad Phi GdUYhHGJ s; (3GdJacjQ GdEHJcGQi s; (3HQfGeL ScGejQs